Okulary Traugutta. Z dziejów przedmiotu i motywu literackiego - Rusin, Joanna (Tematy i Konteksty, 2016)
Romuald Traugutt was short-sighted. He wore glasses from his early years until the last moments of his life. A moment before the execution, he took them off and threw them on the ground. They had survived their owner – today they are kept in the Licheń sanctuary. The motif of Romuald Traugutt’s glasses is a frequent and important component of his literary legend. It appears multiple times in literature – from Gloria Victis by Eliza Orzeszkowa to the poem Gest [Gesture] by Stanisław Grochowiak.